EVALUATION OF ANTI-OBESITY ACTIVITY OF SOLASODINE IN HIGH FAT DIET-INDUCED OBESITY IN RAT - Khaserao, Satish; Somani, Rahul (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study was planned to study the anti-obesity activities of solasodine on high fat (HF) diet-induced obese rats. Methods: Wistar rats were divided into six groups. Control group (Group 1) received normal diet and 0.5 % CMC (5 ml/kg). HF control group (Group 2) received HF diet. Group 3 received orlistat (25 mg/kg body weight per oral). Group 4, 5 and 6 received 25, 50 and 100 mg/kg body weight solasodine respectively. Treatment was given for 6 w to the respective group along with HF diet. Body weight, food intake and abdomen circumference was measured every week for 6 w. On day 42, the serum biochemical parameters like blood glucose and insulin, serum leptin, total cholesterol and triglyceride were evaluated. Animals were sacrificed with overdose of diethyl ether. The liver and retroperitoneal adipose tissues were removed and weighed immediately. Results: Treatment with solasodine at dose of 50 mg/kg and 100 mg/kg significantly (p<0.001) reduced body weight, abdomen circumference and retroperitoneal adipose tissue weight as compared to the HF diet control group. Solasodine also significantly reduced serum total cholesterol, triglyceride and glucose level as compared to HF diet control group (***p<0.001, **p<0.01, *p<0.05 when compared with normal control. ###p<0.001, #p<0.05 when compared with high fat control). In addition, it also inhibited the induction of fatty liver with accumulation of hepatic triglyceride. Conclusion: Solasodine exhibited anti-obesity effect by showing a reduction in body weight, abdomen circumference, total cholesterol level, triglyceride level and glucose level in high-fat diet fed rats.